Blowing-suction type circulating air curtain system - ZHANG YAO; WANG CHUN; LIU JUNRUI; GU ZHENZHEN; ZHU QILU; GUO SHANQI; CHEN PIAOSHI; YUAN BO (2019)
The invention discloses a blowing-suction type circulating air curtain system. The system comprises an upper frame, a lower frame and two air return pipelines. A driving motor and an impeller are arranged in each of the upper frame and the lower frame, wherein the impeller is connected with a motor shaft of the driving motor, so that the driving motor drives the impeller to rotate. Air outlets areformed in the lower side of the upper frame, air inlets are formed in the upper side of the lower frame, and the air outlets directly face the air inlets. The two air return pipelines are located between the upper frame and the lower frame vertically and are close to the two ends of the upper frame and the lower frame, and the two ends of the air return pipelines communicate with the upper frameand the lower frame. The blowing-suction type circulating air curtain system can have a better heat isolating effect, and working medium cyclical utilization can be achieved. 本发明公开了一种吹吸式循环风幕系统，包括上框体、下框体以及两回风管道；所述上框体和下框体内均设有驱动电